A Flexible Two‐Fold Interpenetrated Indium MOF Exhibiting Dynamic Response to Gas Adsorption and High‐Sensitivity Detection of Nitroaromatic Explosives. Issue 20 (3rd July 2019) - Cao, Zhen; Chen, Lian; Li, Shengchang; Yu, Muxin; Li, Zhijia; Zhou, Kang; Liu, CaiPing; Jiang, Feilong; Hong, Maochun
Abstract: A flexible two‐fold interpenetrated indium metal‐organic frameworkInOF‐23, featuring one‐dimensional micro‐sized channels decorated by exposed N groups, was successfully synthesized. Interestingly, InOF‐23 displays unique dynamic responses to different gases (N2, Ar, and CO2 ) at low and room temperatures, which indicates that it can be a good candidate for gas adsorption and separation. Furthermore, the high efficiency detection for p ‐nitroaniline (pNA) makesInOF‐23 a potential chemosensor for nitroaromatic explosives. Abstract : Dynamic response ! A flexible two‐fold interpenetrated indium metal‐organic frameworkInOF‐23 was successfully synthesized.InOF‐23 displays a distinct dynamic response to N2, Ar, and CO2 sorption with different gate opening pressures at low temperature. Moreover, it exhibits fluorescence detection of nitroaromatic compounds with high sensitivities, especially for p ‐nitroaniline.